2005
DOI: 10.2337/diabetes.54.8.2447
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Reduces Glucose-Stimulated Insulin Secretion Rate and Increases Insulin Clearance in Nondiabetic, Insulin-Resistant Individuals

Abstract: Compensatory hyperinsulinemia permitting insulin-resistant individuals to maintain normal glucose tolerance is associated with a left shift in the glucosestimulated insulin secretion rate (GS-ISR) doseresponse curve and decrease in the insulin metabolic clearance rate (I-MCR). To see whether these changes would reverse with improvement in insulin sensitivity, 14 nondiabetic insulin-resistant subjects received rosiglitazone for 12 weeks (4 mg daily for 4 weeks and then 8 mg daily for 8 weeks). Insulin-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 42 publications
7
52
0
Order By: Relevance
“…In Section 4, we consider it as a combination of natural (for example, exercise [38]) and artificial (for example, through use of Rosiglitazone [13]) mechanisms, and as a function of α and β to investigate how it can be used to compensate for the effects of a reduced insulin secretion (α) and/or an increased insulin resistance (β) on an appropriate oscillatory regime.…”
Section: The Two-delay Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Section 4, we consider it as a combination of natural (for example, exercise [38]) and artificial (for example, through use of Rosiglitazone [13]) mechanisms, and as a function of α and β to investigate how it can be used to compensate for the effects of a reduced insulin secretion (α) and/or an increased insulin resistance (β) on an appropriate oscillatory regime.…”
Section: The Two-delay Modelmentioning
confidence: 99%
“…Using the algorithm detailed above, we determine whether each (α,β), with I in as defined by (13) and d i = 0.06, leads to an oscillatory regime. The result is shown in Figure 8.…”
Section: Using Insulin Injections To Stabilise the Glucose Level G *mentioning
confidence: 99%
“…Results from large clinical trials indeed showed that lifestyle changes significantly reduced the incidence of diabetes [26,27]. Thiazolidinediones act as insulin sentitizers by multiple mechanisms and a previous study in non-diabetic insulin resistant individuals indeed demonstrated lower insulin and improvement of insulin resistance after rosiglitazone treatment [28]. In the current study, no additional effect of rosiglitazone on insulin and insulin resistance could be observed, stressing the highly beneficial effects of lifestyle intervention, overshadowing the possible effect of rosiglitazone on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that thiazolidinediones e.g. lower blood glucose levels by enhancing hepatic and peripheral glucose uptake and increase free fatty acid uptake and storage in adipose tissue (thereby decreasing free fatty acid uptake in other tissues) [5,9]. …”
Section: Introductionmentioning
confidence: 99%
“…This action can be either direct, or secondary to the improvement of insulin sensitivity. More recently, rosiglitazone was shown to increase insulin clearance in type 2 diabetic subjects after 12 weeks [2] and 16 weeks [3] of treatment. Although incompletely understood, this effect was considered to be secondary to a decreased liver fat content [3].…”
Section: Introductionmentioning
confidence: 99%